Firn Core Evidence of Two‐Way Feedback Mechanisms Between Meltwater Infiltration and Firn Microstructure From the Western Percolation Zone of the Greenland Ice Sheet. Issue 2 (6th February 2023) - McDowell, Ian E.; Keegan, Kaitlin M.; Wever, Nander; Osterberg, Erich C.; Hawley, Robert L.; Marshall, Hans‐Peter
Abstract: The relationship between firn microstructure and water movement is complex: firn microstructure controls the routing of meltwater through the firn while continuously being altered by liquid water flow processes. Importantly, microstructural transitions within the firn column can stall vertical meltwater percolation, which creates heterogeneities in liquid water content resulting in different rates of firn metamorphism. Physics‐based firn models aim to describe these processes to accurately predict ice layer or firn aquifer formation, but require detailed observations of firn structure to validate and inform percolation schemes. Here, we present grain size measurements and ice layer stratigraphy from seven firn cores collected in western Greenland's percolation zone during the 2016 Greenland Traverse for Accumulation and Climate Studies (GreenTrACS). Grain size transitions within the cores are negatively correlated with all temperature proxies for meltwater supply. Additionally, the number of grain size transitions are strongly anticorrelated with the number of ice layers within each core, despite these transitions, particularly fine‐over‐coarse transitions, promoting meltwater ponding and potential ice layer formation. To investigate if these negative correlations can be understood with firn model physics, we simulate water movement along stratigraphic transitions using the SNOWPACK model. We find that grain size transitions diminish from rapid grain growth in wet firn where ice layers can form, suggesting these microstructural transitions are unlikely to survive repeated meltwater infiltration. Incorporating these microstructure—meltwater feedbacks in firn models could improve their ability to model processes such as ice slab formation or firn aquifer recharge that require accurate predictions of meltwater infiltration depth. Plain Language Summary: As Arctic summers warm, a greater area of the Greenland Ice Sheet (GrIS) melts, including the typically colder, higher‐elevation region where more snow accumulates than melts. Snow that remains after 1 year and is compressed into ice is called firn. Water from melting snow does not immediately run off the ice sheet surface, but it seeps down through interconnected pore‐spaces between firn grains and can eventually freeze, forming ice layers. We can explore the physical properties of firn that cause ice layers to form by examining firn cores. Ice layers often form along boundaries where firn grains change size, particularly where smaller grains overlie larger grains. We examine seven shallow firn cores from the GrIS to investigate how grain sizes determine where ice layers form. Firn cores containing numerous ice layers that have fewer grain size transitions than cores lacking many ice layers. We use computer simulations to demonstrate that grains grow faster in wet firn from water ponding along these transitions than in dry firn below. Therefore, grain size transitions disappear where water accumulates and, if refreezing occurs, an ice layer forms. We suggest firn modelers account for grain size changes when modeling water movement in firn. Key Points: Grain size transitions are anticorrelated with the number of ice layers and temperature proxies for melt in western Greenland firn cores Model‐simulated water flow and grain growth show a decreasing grain size contrast along microstructural transitions during water percolation Low numbers of grain size transitions in firn cores can indicate a previous wetting history of the firn layer